MORPHOMETRIC STUDIES OF ATRIOVENTRICULAR VALVE IN COMBINED MITRAL HEART DISEASE - Stepanchuk, A.P. (World of Medicine and Biology, 2012)
We studied eight drugs hearts of people who died at the age of 34 to 90 years of combined acquired mitral heart disease due to rheumatic fever. For morphometric methods determined the basic metric parameters of mitral and tricuspid valves, as well as the total number of tendinous chords are fixed to the shutters of valves. When combined mitral valve is a thickening and shortening of its wings, which entails no elongation and shortening, with a proportional-valve papillary thickening of the tendon of the chords and the corresponding tightening of the valve to the boundary zone of the apical parts of hypertrophied papillary muscles. When combined mitral stenosis with a predominance of vice diameter of the left atrio-ventricular opening is reduced (2,45 ± 0,05 cm) and the right increased (4,20 ± 0,04). In mitral insufficiency with a predominance of vice valve diameter increases and the right (4,12 ± 0,04 cm) and left (3,96 ± 0,03 cm), atrio-ventricular openings.